Immediate titanium mesh implantation for patients with postcraniotomy neurosurgical site infections: safe and aesthetic alternative procedure? - Ehrlich, Gregory Marius; Kindling, Stefanie; Wenz, Holger; Hänggi, Daniel; Schulte, Dirk Michael; Schmiedek, Peter; Seiz-Rosenhagen, Marcel (World neurosurgery, 2017)
Background Surgical site infection (SSI) is one of the main complications after craniotomy. The incidence is up to 11% in the literature. The established procedure is debridement, removal of the bone flap, and delayed cranioplasty. Delayed cranioplasty has several disadvantages. A promising approach is the immediate titanium mesh implantation at the time of wound revision. We report our experience with this technique regarding outcome measured by reinfection rates and patient satisfaction. Methods Patients treated in our department from January 2013 to October 2014 with SSI after craniotomy for brain tumor, trauma, or vascular pathologies were prospectively collected. In all these patients, immediate titanium mesh implantation after bone flap removal was performed. Primary outcome parameters were the reinfection rate and patient satisfaction via self-designed questionnaires in a follow-up period >3 months. Results Twenty-four patients were included within the study period. Main risk factors causing SSI were previous steroid medication (62.5%), cranial radiation therapy (42%), cerebrospinal fluid fistula after initial surgery (12.5%), and diabetes mellitus (25%). The follow-up was >3 months after titanium mesh cranioplasty (mean 4.6 months; range 3-6 months). No recurrent infection was detected in the study group. In 2 cases, reoperation was necessary. The returning questionnaires showed a high satisfaction rate with the cosmetic result. Conclusions Our small series seems to confirm that immediate titanium mesh implantation for patients with postcraniotomy SSI is a cost-effective, safe, and cosmetically suitable alternative to delayed cranioplasty in selected patients without hydrocephalus or persistent cerebrospinal fluid fistula.